With 8D method to excellent quality - Krajnc, Marjanca (Revija za univerzalno odličnost, 2012)
RQ: The research aims to establish the suitability of the 8D methodology for complaint settlement, and to identify any resulting improvement in quality. Purpose: Studies that have research the 8D method are scarce in international literature. Consequently, we decided to assess, based on theoretical premises, the suitability of the 8D method used by an organization, and the efficiency of quality performance directly associated with the 8D method. We will establish whether the use of the 8D method results in quality improvement. Method: The research will be carried out using qualitative analysis in the form of a case study of the 8D method used in an organization. I will discuss, based on real and relevant data, the approaches implemented by individual 8D method steps, indicating the integrated supplemental tools. In the quantitative part, I will identify the defective product trends (PPM) and the trends of costs related to defective products. Results: The 8D method used for complaint settlement contributes to improved quality and company performance. Organization: The results can be used by the management in continuous improvement as additional motivation for more consistent and effective use, and for additional support to problemsolving coordinators and teams. Society: The findings can also be applied by society at large, mostly companies and public services. Originality: Research on this topic or combination has not yet been conducted Limitations: The sample studied is small, limited to one large company. It includes only the data obtained through the use of the 8D method.
Keywords: kvaliteta; management; metode; podjetja; reševanje problemov; vodenje; zagotavljanje kvalitete